2011
DOI: 10.1021/jp1105746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Different CeO2 Structures on Mesoporous Silica and Characterization of Their Reduction Properties

Abstract: An investigation was performed to establish the effects of precursor composition on the structure of ceria deposited onto mesoporous silicas, MCM-41 and SBA-15. The structure of the deposited ceria was characterized by XRD, TEM, Raman and UV-visible spectroscopy, XANES, and EXAFS. Using Ce(acac) 3 as the precursor resulted in formation of 3 nm diameter ceria particles located predominantly in the mouths of the support pores. Amorphous agglomerates, but with domains of comparable size to those obtained using Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 106 publications
3
41
0
1
Order By: Relevance
“…The major peaks in the PL spectra of the pristine and sunlight exposed CeO 2 appeared at 453 nm, 470 nm, 483 nm, 493 nm and 550 nm (Figure 3b). The mild variation in the observed values and that reported in the literature [43,44], may be attributed to variation in synthetic route and calcination conditions. Instead of discussing the origin, we concentrated on the variation in the intensity of these emission peaks for pristine and sunlight exposed CeO 2 .…”
Section: Photocatalytic Degradation Of Phenolic Substratesmentioning
confidence: 47%
“…The major peaks in the PL spectra of the pristine and sunlight exposed CeO 2 appeared at 453 nm, 470 nm, 483 nm, 493 nm and 550 nm (Figure 3b). The mild variation in the observed values and that reported in the literature [43,44], may be attributed to variation in synthetic route and calcination conditions. Instead of discussing the origin, we concentrated on the variation in the intensity of these emission peaks for pristine and sunlight exposed CeO 2 .…”
Section: Photocatalytic Degradation Of Phenolic Substratesmentioning
confidence: 47%
“…Depending on the surface concentration, two different oxide species exist: isolated species at a low content and agglomerated species with excess loading [27]. Alkoxide precursors are usually preferred over acetylacetonates when the aim is the synthesis of isolated sites by means of grafting, because previous work has indicated that acetylacetonates might lead to the formation of agglomerates already at lower loadings [28,29]. Owing to different chemical states, the catalytic behaviors of the two species for specific reactions may differ greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The sample fabricated with 1.5 wt% CeO 2 in the precursor showed a 30% enhancement of its UV absorption capacity as compared to commercial TiO 2 nanoparticles with a wavelength of 300 nm. This can be attributed to the porous structure of the CeO 2 ASiO 2 composite particles for UV absorption, which can prevent potential damage from UV light and restrain the unnecessary surface activity of the CeO 2 [15,16]. It should be noted that the aerosol process caused the porous CeO 2 ASiO 2 composite particles with more than 0.75 wt% of CeO 2 in the precursor to show high UV absorption ability.…”
Section: Resultsmentioning
confidence: 99%
“…When CeO 2 ASiO 2 composite particles are prepared, the SiO 2 nanoparticles enhance the coverage on the skin and give the skin a natural color. The CeO 2 ASiO 2 composite particles not only enhance the thermal stability but also increase the surface area [15,16]. The use of these particles is known to be an efficient way to improve the activity of UV absorption as well.…”
Section: Introductionmentioning
confidence: 99%